The implantation of cork oak (Quercus suber L) make use of herbicides: Preliminary results (CONGRESS 1997 - SOCIEDAD ESPANOLA DE MALHERBOLOGIA, PROCEEDINGS, 1997)
The response of cork oak (Quercus suber L.) to different rates of hexazinone, simazine and pendimetaline herbicides applied with a logaritmic sprayer, was studied. The effect on weeds of these herbicicles was also studied.